Examining Family Atmosphere and School Climate Within Psychology of Working Theory Among Chinese Rural College Students - Lu Hai; Xiaohong Bao; Yang Wang; Mengxiao Zhang; Man Shu (Behavioral Sciences)
The employment situation for college students has worsened due to the increase in the number of graduates and the impact of the COVID-19 pandemic on the economy. Consequently, the pressure to find employment has also increased, particularly for rural college students. Drawing on the Psychology of Working Theory (PWT), the present study was performed to examine the applicability of some proposed pathways in the PWT and test the relationships between family atmosphere and school climate and work volition, career adaptability, and future decent work perception within 946 rural college students (243 men and 703 women; Mage = 19.86, SD = 1.48). The study employed a cross-sectional research design, and structural equation modeling (SEM) was used. Results indicated that family atmosphere and school climate significantly positively predict work volition, career adaptability and future decent work perception. Work volition significantly predicts career adaptability and future decent work perception. Moreover, our findings supported the mediating effect of work volition, indicating that family atmosphere and school climate increased career adaptability and future decent work perception by improving work volition. Although this study has limitations, it informs future studies by highlighting the important role of family atmosphere, school climate, and work volition.